A Two-tiered Approach for Knowledge Reasoning - Pinto, Fernando Antonio Dantas Gomes; Santos, Jefferson de Barros; Lifschitz, Sergio; Haeusler, Edward Hermann (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
This article proposes an explicit two-tier approach for reasoning and querying on Knowledge Bases. It separates the conceptual fraction from the model elements, enabling clear connections between the components. This method may be more effective than known one-tier solutions. Besides a theoretical view, we explore a case study on actual data about legal knowledge to illustrate how well our strategy may work in practice.